2023
DOI: 10.3390/ma16114155
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Mg Alloy with Multiple RE Elements with Ag and Zn Doping via Heat Treatment

Abstract: Strengthening Mg alloys with rare earth elements has been a research focus for several decades. To minimize the usage of rare earth elements while enhancing mechanical properties, we adopted the strategy of alloying with multiple rare earth elements, namely Gd, Y, Nd, and Sm. Additionally, to promote the precipitation of basal precipitate, Ag and Zn doping was also induced. Thus, we designed a new cast Mg-2Gd-2Y-2Nd-2Sm-1Ag-1Zn-0.5Zr (wt.%) alloy. The microstructure of the alloy and its relevance to mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, the low plasticity at room temperature, poor heat, and poor corrosion resistance of traditional magnesium alloys limits their wide application [ 1 , 2 , 3 , 4 , 5 ]. Alloying is an effective method to improve the mechanical properties of magnesium alloys [ 6 ]. Previous studies have shown that, when Sn is added to magnesium, the Mg 2 Sn phase formed has a high melting point and high hardness, which can effectively improve the mechanical properties and thermal stability of the alloy, as well as improve the high-temperature strength and creep resistance of magnesium alloys [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the low plasticity at room temperature, poor heat, and poor corrosion resistance of traditional magnesium alloys limits their wide application [ 1 , 2 , 3 , 4 , 5 ]. Alloying is an effective method to improve the mechanical properties of magnesium alloys [ 6 ]. Previous studies have shown that, when Sn is added to magnesium, the Mg 2 Sn phase formed has a high melting point and high hardness, which can effectively improve the mechanical properties and thermal stability of the alloy, as well as improve the high-temperature strength and creep resistance of magnesium alloys [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%